Ecological distribution and population features of Hexapanopeus paulensis Rathbun, 1930 (Crustacea: Decapoda: Xanthoidea) caught by bottom trawling in the southeastern coast of Brazil: implications for its population structure - Silva, Thiago Elias Da; Frameschi, Israel Fernandes; Almeida, Ariadine Cristine; Fransozo, Vivian; Bertini, Giovana; Taddei, Fabiano Gazzi (Sociedade Brasileira de Carcinologia, 2017)
ABSTRACT We analyzed the spatio-temporal variations of the abundance, distribution and the population structure of Hexapanopeus paulensis Rathbun, 1930 from the southeastern Brazilian coast. Monthly samples were taken from January 1998 to December 1999 at Ubatumirim, Ubatuba and Mar Virado bays. A total of 1084 individuals were obtained, 76 specimens at Mar Virado, 322 at Ubatuba and 686 at Ubatumirim. It was possible to verify an association between the abundance of H. paulensis and bottom temperature (positive correlation), grain size of sediment and organic matter content (both negatively). This explains the higher number of individuals in the stations nearest to the continent (with higher temperature values and heterogeneous substrate). Juveniles were recorded throughout the study period, constituting 39.5% of the sampled population, which highlights the importance of the region (especially Ubatumirim Bay, due the highest abundance) for the establishment of the species. Only females occupied the largest size classes, which could mean differential mortality between the sexes or growth rate. Nevertheless, further studies should be accomplished to a better comprehension of such difference.
Keywords: Panopeidae; environmental variables; recruitment; sex ratio